Evaluation by microarray of the potential safety of Sarracenia purpurea L. (Sarraceniaceae) a traditional medicine used by the Cree of Eeyou Istchee - Carolina Cieniak; Charlotte McDonald; John Nash; Asim Muhammad; Alaa Badawi; Pierre S Haddad; Alain Cuerrier; Steffany A.L. Bennett; Brian C Foster; John T Arnason (Frontiers Media S.A., 2015)
Purpose: The purpose of this study was to assess safety of the traditional antidiabetic extracts of either S. purpurea or its lead active principle, morroniside at the transcriptional level. The overarching objective was to profile and validate transcriptional changes in the cytochrome P450 family of genes, in response to treatment with S. purpurea ethanolic extract or its lead active, morroniside. Methods: Transcriptional activity was profiled using a 19K human cDNA microarray in C2BBe1 cells, clone of Caco-2 intestinal cells, which are a model of first-pass metabolism (1, 2). Cells were treated with S. purpurea extract for 4 and 24 hrs, as well as the pure compound morroniside for 4 hrs, to determine their effects. Results:  No evidence of cytochrome P450 transcriptome regulation or of transcriptional activation of other diabetes relevant mRNA was detected after rigorous quantitative-PCR validation of microarray results. Conclusion: Our data do not support a transcriptional mechanism of action for either S. purpurea extract or its lead active, morroniside.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.